2018
DOI: 10.1016/j.juro.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Robotic Assisted Microsurgical Denervation of the Spermatic Cord for the Treatment of Chronic Orchialgia or Groin Pain: A Single Center, Large Series Review

Abstract: Targeted robotic assisted microsurgical denervation of the spermatic cord is an effective, minimally invasive approach with potential long-term durability in patients with refractory chronic orchialgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Therefore, the treatment of chronic nonspecific CO is to remove or change the hyperactivated nerve pathways in the spermatic cord, so the targeted MDSC can be a successful option to treat CO. And our results show that targeted MDSC is effective in outcomes. However, numerous studies show variable success rates [1,9,10,23,24]. The PIQ-6 questionnaire showed that most patients had a significant pain relief after MDSC, and only 17.9% of patients continued to have postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the treatment of chronic nonspecific CO is to remove or change the hyperactivated nerve pathways in the spermatic cord, so the targeted MDSC can be a successful option to treat CO. And our results show that targeted MDSC is effective in outcomes. However, numerous studies show variable success rates [1,9,10,23,24]. The PIQ-6 questionnaire showed that most patients had a significant pain relief after MDSC, and only 17.9% of patients continued to have postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…A standard MDSC needs (1) identification of the testicular, cremasteric, and deferential arteries, (2) ligation of the internal spermatic veins, (3) division of all cremasteric musculature and spermatic cord fascia, and (4) preservation of a few lymphatics [9,10]. Parekattil et al [2] performed a study comparing patients with CO to those without.…”
Section: Introductionmentioning
confidence: 99%
“…A significant barrier to the scientific evaluation of a condition and its treatment is the lack of a standardized and validated way to assess and quantify symptoms. Currently, the orchialgia literature uses subjective measures of patient improvement, visual analogue scales for pain or other pain instruments not designed or validated for this type of pain such as the PIQ-6 ( 4 ). Furthermore, simple pain scales may fail to incorporate other features of the condition that also impact QOL.…”
Section: Discussionmentioning
confidence: 99%
“…The development of validated symptom scores is especially important in subjective disorders; development of such instruments in voiding dysfunction, sexual dysfunction and prostatitis has led to more widespread scientific study in these conditions. Most studies to date have either used a trinary “gone”, “improved” or “unchanged” outcome ( 3 ) or a pain scale not validated for orchialgia ( 4 ). This may fail to adequately encompass the patient experience in chronic pain disorders, which can represent a complex interaction of a constellation of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous groups have published success rates ranging from 77–100% in terms of significant reduction or elimination of pain. 18 , 21 , 22 , 47 , 62 The trifecta nerve complex mentioned in the pathophysiology section above explains the benefit of MDSC in CSP patients. Ligation of the nerves with Wallerian degeneration in the trifecta is likely to provide pain relief or reduction in CSP patients undergoing MDSC.…”
Section: Treatment Algorithm For Chronic Orchialgia or Chronic Scrotamentioning
confidence: 99%